Positive accounting theory - Watts, Ross L. (Prentice-Hall, 1986)
This book presents the theory and methodology underlying the economic-based empirical literature in accounting. The concept of theory underlying that literature is the scientific concept of theory; the objective of theory is to explain and predict phenomena (in this case, accounting practice). In economics, that concept has come to be called "positive theory". The book begins with the introduction of the concept of positive theory and scientific methodology form finance and ends with the studies in which researchers ask the crucial question for an accounting theorist: Why is accounting and auditing practice like it is?